Pendidikan Kesehatan Persiapan Menghadapi Menopause Pada Ibu-Ibu Usia Premenopause Di Sungai Pagar, Kabupaten Kampar - Neni Ristiani; Mofri Lindo; Risnandar Risnandar; Huda Marlinawati; Neni Triana (Compromise Journal Community Proffesional Service Journal, 2024)
Menopause is a physiological process that every woman will go through. During menopause, many changes occur in a woman's body, both physical and psychological. The changes that occur during menopause tend to cause discomfort, therefore menopause is a process that is quite a burden for a woman. Fear of facing menopause should be minimized if someone has sufficient knowledge about the menopause process and the complaints that can arise during menopause as well as the efforts that can be made to overcome these complaints.